A cross sectional study to investigate internal hernia post left-sided colectomy preserving superior rectal artery. (December 2019) - Taira, Tetsuro; Murono, Koji; Nozawa, Hiroaki; Hojo, Daisuke; Kawai, Kazushige; Hata, Keisuke; Tanaka, Toshiaki; Ishihara, Soichiro
Abstract: Background: and Purpose: Intestinal obstruction caused by an internal hernia projecting through a mesenteric defect is a rare sequela of laparoscopic colectomy, as surgeons usually leave such defects open. In this study, we investigated cases of internal hernia after laparoscopic left-sided colectomy. Methods: Data of 308 patients who underwent laparoscopic left hemicolectomy or sigmoidectomy at our institute between 2013 and 2018 were retrospectively reviewed. Patient characteristics and surgical variables were analyzed. The distance between the superior rectal artery (SRA) and abdominal aorta at the level of aortic bifurcation was measured using postoperative computed tomography in patients who underwent SRA-preserving colectomy. Results: In all, 3 patients (0.97%), all of whom had undergone colostomy without anastomosis and with SRA preservation, developed internal hernia passing between the SRA and the aorta. The distance between the SRA and abdominal aorta in patients who underwent ostomy was significantly more than that in patients who underwent non-ostomy (10.6 mm vs. 4.7 mm, respectively, p < 0.001). Conclusions: SRA preservation and stoma construction are potential risk factors for internal hernia after laparoscopic left-sided colectomy. Lifting of the SRA due to stoma construction possibly enlarges the space between the SRA and aorta. When colostomy is created, it is important to evaluate the space behind the SRA. Highlights: Internal hernia projecting through a mesenteric defect is a rare sequela of laparoscopic colectomy, as surgeons usually leave such defects open. However, leaving a residual defect may increase the incidence of internal hernia. In this study, we assessed the cases of internal hernia after laparoscopic colectomy.